Endoscopic Submucosal Dissection for Gastric Subepithelial Tumors: A Single-Center Experience - Jin Sung Lee; Gwang Ha Kim; Do Youn Park; Jong Min Yoon; Tae Wook Kim; Jong Hun Seo; Bong Eun Lee; Geun Am Song (Gastroenterology Research and Practice)
Background and Aims. Endoscopic submucosal dissection (ESD) has been accepted as a treatment modality for gastrointestinal epithelial tumors. Recently, ESD has been applied to resect subepithelial tumors (SETs) in the gastrointestinal tract, but clinical evidence on its efficacy and safety is limited. The aim of this study was to investigate the efficacy and safety of ESD for gastric SETs and to assess possible predictive factors for incomplete resection. Patients and Methods. Between January 2006 and December 2013, a total of 49 patients with gastric SET underwent ESD at our hospital. Clinicopathologic characteristics of patients and SETs, therapeutic outcomes, complications, and follow-up outcomes were evaluated. Results. The overall rates of en bloc resection and complete resection were 88% (43/49) and 84% (43/49), respectively. Complete resection rates in tumors originating from the submucosal layer were significantly higher than those in tumors originating from the muscularis propria layer (90% versus 56%, P=0.028). In multivariate logistic regression analyses, tumor location (upper third: odds ratio [OR] 12.639, 95% confidence interval [CI] 1.087–146.996, P=0.043) and layer of tumor origin (muscularis propria: OR 8.174, 95% CI 1.059–63.091, P=0.044) were independently associated with incomplete resection. Procedure-related bleeding and perforation rates were both 4%. No recurrence was observed in patients with complete resection at a median follow-up period of 29 months (range: 7–83 months). Conclusions. ESD is an effective, safe, and feasible treatment for gastric SETs. The frequency of incomplete resection increases in tumors located in the upper third of the stomach and in those originating from the muscularis propria layer.